The Abundance and the Distribution Pattern of Sucker Snail (Cerithidea quadrata) in Mangrove Forest of Untut Island of Teluk Meranti District of Pelalawan Regency of Riau Province - Suzila '; Efriyeldi '; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in October 2015. The samples were taken in mangrove forest of Untut Island of Teluk Meranti District of Pelalawan Regency of Riau Province. The sample was analyzed in the Laboratory of Marine Chemistry and Laboratory of Marine Biology of Faculty of Fisheries and Marine Sciences, University of Riau. The result showed the average of sucker snail (C. quadrata) in each station ranged from 1-6.22 ind/m2. The abundance of C. quadrata among station I, station II and III was not different significanty (p<0.01) while in station II and III was different significanty (p>0.05). The most dominant individual size of C. quadrata was found in station 3 (2-3.99 cm) which comprising of 64 individuals. The distribution pattern of C. quadrata in each station in the research area was in the from of groups.Keywords: Abudance, distribution of gastropods, mangrove forest, Untut Island.